Macbeth - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. No fear Shakespeare graphic novels., 2008)
An adaptation of Shakespeare's drama of an ambitious man whose unscrupulous wife urges him to murder in order to seize the throne of Scotland.